2022
DOI: 10.1186/s40635-022-00461-8
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic responses to exercise in survivors of critical illness: an exploratory pilot study

Abstract: Background ICU survivors suffer from impaired physical function and reduced exercise capacity, yet the underlying mechanisms are poorly understood. The goal of this exploratory pilot study was to investigate potential mechanisms of exercise limitation using cardiopulmonary exercise testing (CPET) and 6-min walk testing (6MWT). Methods We enrolled adults aged 18 years or older who were treated for respiratory failure or shock in medical, surgical, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Six months after critical illness has been overcome, mitochondrial content may restore up to normal, but structural and possibly functional impairments might persist over months, accompanied by marked muscle weakness and wasting [ 83 , 195 ]. This is supported by recent data showing that even few days of critical illness may contribute to significant alterations of mitochondrial respiratory activity up to 6 months after ICU admission [ 196 ]. Considering the dynamics of mitochondrial dysregulation during the course of critical illness, several interesting attempts can be made to restore and improve mitochondrial function and patient outcome.…”
Section: Dynamics Of Mitochondrial Alterations and Therapeutic Implic...supporting
confidence: 69%
“…Six months after critical illness has been overcome, mitochondrial content may restore up to normal, but structural and possibly functional impairments might persist over months, accompanied by marked muscle weakness and wasting [ 83 , 195 ]. This is supported by recent data showing that even few days of critical illness may contribute to significant alterations of mitochondrial respiratory activity up to 6 months after ICU admission [ 196 ]. Considering the dynamics of mitochondrial dysregulation during the course of critical illness, several interesting attempts can be made to restore and improve mitochondrial function and patient outcome.…”
Section: Dynamics Of Mitochondrial Alterations and Therapeutic Implic...supporting
confidence: 69%
“…Two reports found decreased VT and increased lactate levels after COVID-19, whereas other studies found no difference in VT between patients with PCC and control participants . Importantly, the former studies included patients with relevant comorbidities, hospitalizations, and occasionally intensive care or mechanical oxygen support, factors that are known to have adverse effects on peripheral muscle tissue …”
Section: Discussionmentioning
confidence: 99%
“…Changes in HR between devices that led to a difference in numerical precision could be explained by a change in position from supine to sitting with an exaggerated response in relation to deconditioning, autonomic disturbances, as well as rapid changes in clinical status that can occur in ICU patients. Resting heart rate might be faster in a sitting position compared with lying, and variations in heart rate as well as QTc interval and dispersion can be produced by postural changes, especially in critically ill patients who may develop physical deconditioning and orthostatic intolerance (Aglawe et al., 2022 ; Borst et al., 1982 ; Fortrat et al., 1999 ; Jones et al., 2003 ; Levine et al., 1997 ; Mart et al., 2022 ; Nakagawa et al., 1999 ). Even though formulas try to correct QT according to heart rate, rapid changes in the R‐R interval secondary to position changes might not be adequately corrected by them (Kubo et al., 2005 ; Markendorf et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%